2017
DOI: 10.1111/bjop.12274
|View full text |Cite
|
Sign up to set email alerts
|

Development of motor imagery ability in children with developmental coordination disorder – A goal‐directed pointing task

Abstract: Children with developmental coordination disorder (DCD) have difficulties with the predictive control of movements. This was shown in studies that target motor imagery and motor planning, and appears to become particularly evident with increases in task complexity. In this study, we used a complex mental chronometry paradigm to examine the development of motor imagery ability in children with DCD, using a longitudinal design. Thirty children were included in the DCD group (aged 6-11 years) and age- and gender-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
(98 reference statements)
0
9
0
1
Order By: Relevance
“…Motor Imagery, Action Observation, Imitation, and Gesture Production Both implicit and explicit MI were investigated in seven studies (six of high quality, and one moderate), with a moderate overall effect (d = 0.61, 95% CI [0.35, 0.88]) (Adams et al, 2017a(Adams et al, ,b, 2018Kashuk et al, 2017;Fuchs and Cacola, 2018;Hyde et al, 2018;Scott et al, 2019). The combined ESs are presented in Figure 6.…”
Section: Dynamical/ecological Paradigms-rhythmic Coordination and Ecological Perceptionmentioning
confidence: 99%
“…Motor Imagery, Action Observation, Imitation, and Gesture Production Both implicit and explicit MI were investigated in seven studies (six of high quality, and one moderate), with a moderate overall effect (d = 0.61, 95% CI [0.35, 0.88]) (Adams et al, 2017a(Adams et al, ,b, 2018Kashuk et al, 2017;Fuchs and Cacola, 2018;Hyde et al, 2018;Scott et al, 2019). The combined ESs are presented in Figure 6.…”
Section: Dynamical/ecological Paradigms-rhythmic Coordination and Ecological Perceptionmentioning
confidence: 99%
“…The development of MI ability has been extensively studied in children without impairments [ 42 , 50 ]. More recently, a few studies on MI ability in children with motor deficits such as development coordination disorder (DCD) [ 51 , 52 , 53 ] or cerebral palsy (CP) have been conducted [ 54 ]. DCD is a neurodevelopmental condition that is characterized by the inability to acquire and execute well-coordinated movements at an age-appropriate level [ 55 ], reflected by slow, effortful, inaccurate and ill-coordinated movements [ 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mental simulation techniques like motor imagery and action observation (i.e., the structured observation of action execution) have been proposed to be effective interventions that target internal model deficits (Adams, Lust & Steenbergen, 2018). These interventions have shown promise in improving movement outcomes in sporting tasks (Cumming & Ramsey, 2009) and for clinical conditions like Parkinson's disease (Caligiore, Mustile, Spalletta, & Baldassarre, 2017), stroke (Ertelt & Binkofski, 2012;Zimmermann-Schlatter, Schuster, Puhan, Siekierka, & Steurer, 2009) and for children with cerebral palsy (Buccino et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These interventions have shown promise in improving movement outcomes in sporting tasks (Cumming & Ramsey, 2009) and for clinical conditions like Parkinson's disease (Caligiore, Mustile, Spalletta, & Baldassarre, 2017), stroke (Ertelt & Binkofski, 2012;Zimmermann-Schlatter, Schuster, Puhan, Siekierka, & Steurer, 2009) and for children with cerebral palsy (Buccino et al 2018). It has also been suggested that mental simulation techniques may be beneficial for children with DCD (Adams et al, 2018) and a small number of studies have reported positive outcomes. For example, Wilson, Thomas and Maruff (2002) found that motor imagery training was equally as effective as traditional perceptual motor training for developing motor skills, particularly with children with severe DCD (Wilson, Adams, Caeyenberghs, Thomas, Smits-Engelsman & Steenbergen, 2016).…”
Section: Introductionmentioning
confidence: 99%